Public Attitudes Toward Breastfeeding in Public Places in Ottawa, Canada. (May 2017) - Russell, Katherine; Ali, Amira
Background: In Ontario, Canada, breastfeeding in public is a protected right, yet even with these laws, attitudes toward breastfeeding in public can serve as a barrier to breastfeeding. Research aim: This study assesses public support for breastfeeding in public among adults in Ottawa, Ontario, and examines sociodemographic associations with negative attitudes toward public breastfeeding. Methods: Data from the 2015 Rapid Risk Factor Surveillance System (RRFSS), a population health telephone survey, were obtained for Ottawa. Adults ages 18 years and older were asked whether it was acceptable for a mother to breastfeed her baby in a restaurant and shopping mall ( n = 1, 276). Descriptive statistics and regression were used to describe sociodemographic characteristics associated with negative attitudes. Results: Overall, 75% of respondents agreed that it was acceptable for a mother to breastfeed her baby in both a restaurant and shopping mall (restaurant: 78%; shopping mall: 81%). Respondents who did not have children at home, were less educated, had a mother tongue language other than French or English and who were retirees were less likely to support breastfeeding in restaurants and shopping malls. In addition, women and immigrants living in Canada for more than 15 years were less likely to support breastfeeding in shopping malls. Conclusion: Despite a law to support public breastfeeding in Ontario, there is room to improve attitudes toward public breastfeeding. Increased public support for public breastfeeding can support women and children to achieve their feeding goals, particularly for those wanting to exclusively breastfeed.